Weighing the world the Reverend John Michell of Thornhill / Russell McCormmach. - McCormmach, Russell (Archimedes (Dordrecht, Netherlands), 2012)
The book about John Michell (1724-93) has two parts. The first and longest part is biographical, an account of Michell's home setting (Nottinghamshire in England), the clerical world in which he grew up (Church of England), the university (Cambridge) where he studied and taught, and the scientific activities he made the center of his life. The second part is a complete edition of his known letters. Half of his letters have not been previously published; the other half are brought together in one place for the first time. The letters touch on all aspects of his career, and because they are in h.